2020
DOI: 10.1111/dth.14461
|View full text |Cite
|
Sign up to set email alerts
|

Sweet syndrome as an adverse reaction to tyrosine kinase inhibitors: A review

Abstract: Tyrosine kinase inhibitors are a class of targeted anticancer drugs that inhibit cancer cell proliferation by inactivating proteins involved in signal transduction cascades. Various cutaneous adverse events have been observed after tyrosine kinase inhibitor administration, including Sweet syndrome. We queried the PubMed database to identify 14 cases of Sweet syndrome thought to be secondary to tyrosine kinase inhibitors. Tyrosine kinase inhibitor‐induced Sweet syndrome had a median of 2 months latency followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Anti-TNF-α therapy has been proven effective in Sweet’s syndrome with coexisting inflammatory bowel disease, Sjogren’s syndrome [ 16 ], and RA [ 17 ]. Yang et al have reported tyrosine kinase inhibitor-induced Sweet’s syndrome with a median of two months' latency period [ 18 ]. Our patient developed Sweet’s syndrome two months after the initiation of adalimumab.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-TNF-α therapy has been proven effective in Sweet’s syndrome with coexisting inflammatory bowel disease, Sjogren’s syndrome [ 16 ], and RA [ 17 ]. Yang et al have reported tyrosine kinase inhibitor-induced Sweet’s syndrome with a median of two months' latency period [ 18 ]. Our patient developed Sweet’s syndrome two months after the initiation of adalimumab.…”
Section: Discussionmentioning
confidence: 99%
“…Minocycline has been reported to be less frequent [ 5 ]. Recently, SS has also been described as an adverse effect of tyrosine kinase inhibitors [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…While most commonly associated with colony-stimulating factors (e.g., G-CSF), drug-induced SS has been reported to a variety of medications. Notable cancer therapies include ATRA, FLT-3 inhibitors, immune checkpoint inhibitors, and tyrosine kinase inhibitors [3,14,16,17,[41][42][43][44][45].…”
Section: Epidemiologymentioning
confidence: 99%